Design, synthesis, and biological evaluation of PqsR antagonists guided by classic hit-to- lead optimisation process and fragment- based methods for the treatment of Pseudomonas aeruginosa infections - Liu, Ruiling (2021)
Pseudomonas aeruginosa (P. aeruginosa) a nosocomial pathogen, has become a serious public health threat due to its high mortality rates and serious antibiotic resistance issue. The Pseudomonas quinolone signal (pqs) system of P. aeruginosa is essential in regulating the biosynthesis of virulence factors. The transcriptional regulator of pqs system PqsR has been regarded as an interesting research topic for the treatment of P. aeruginosa infections. This thesis is focused on using multiple hit-to-lead optimization methods to find novel PqsR antagonists to overcome P. aeruginosa infections. Chapter 1 provides background information about P. aeruginosa pathogenicity, the pqs system and current progress towards finding PqsR antagonists. An overview of fragment-based lead discovery (FBLD) including hit identification, fragment library construction, biophysical methods and hit-to-lead evolution methods is also provided. Chapter 2 describes a classic hit-to-lead optimisation process starting from the virtual screening of an in-house compound library against PqsR protein to obtain 19. Compound 19 displayed good hit likeness and was subjected to hit-to-lead optimization to achieve a potent drug sized PqsR antagonist 69 with IC50 values of 0.25 μM and 0.34 μM in PAO1-LmCTX::PpqsA-lux and PA14mCTX::PpqsA-lux reporter assays respectively. The X-ray crystal structure of the 69-PqsR LBD complex was also obtained, which provides insights into specific ligand-target interactions. Chapter 3 focuses on fragment-based methods in the discovery of PqsR antagonists. Assisted by in silico methods, five fragment libraries were screened against PqsR protein and the high scoring fragments were subjected to a thermal shift assay (TSA) to give fragment hits 106, 107. Through hit exploration study, fragments 106, 107 were optimised and led to the identification of fragments 145a, 145c and 146b displaying improved biophysical profiles and these fragments can act as good starting points for the identification drug-sized PqsR antagonists (350 < MWt < 500). Chapter 4 demonstrates the evolution of fragment hits 106, 149, 145a, 145c and 146b to drug-sized molecules through fragment linking, merging, and growing methods. Applying a fragment growing method on 106 led to the discovery of 148b and 148c displaying pqs inhibition observed as remaining activity (RA%) values of 60% and 63% at 50 μM screening concentration in PAO1-LmCTX::PpqsA-lux reporter assays, respectively. Linking fragment 146b and 152a led to the discovery of compound 154b showing a RA% value of 34% at 10 μM screening concentration. It was hypothesized that two fragments bound to the PqsR LBD in different sub-pockets can functionalize as synergistic combinations observed as the fragment cocktails displaying a greater effect in bioreporter assay and biophysical experiments than the single fragments. A synergistic exploration experiment was designed assisted by TSA and mCTX::PpqsA-lux based bioreporter assay and led to the identification of two pairs of synergistic combinations (81 and 108, 81 and 105) showing improved in vitro or biophysical profiles in combination than in single fragments.